Case report on hereditary haemorrhagic telangiectasia - Mathur, Stuti; Saberwal, Akanksha; Dabholkar, Yogesh; Verma, Bhavika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Osler Weber Rendu disease also known as hereditary haemorrhagic telangiectasia (HHT) is a rare autosomal dominant disorder by the presence of multiple arteriovenous malformations (AVMs) that lack intervening capillaries resulting in direct connections between arteries and veins. A 70-year-old male patient known case of hypertension; Indian origin was brought to the emergency department of our hospital with complaints of severe epistaxis. An attempt was made initially to control bleeding by ice compressions and finally anterior and posterior nasal packing was done. He gave history of similar episodes in the past often accompanied with hemetemesis and malena on and off since childhood gastroduodenoscopy was done to rule out cause for hemetemesis which showed multiple telangiectasia in fundus, body and antrum of stomach and first part of duodenum establishing the diagnosis of HHT. Patient with Osler-Weber–Rendu disease may present with uncontrolled bleeding. Resuscitation along with hemostasis is the main stay of treatment. As the bleeding occurs from malformed vessels coagulation tests are normal. Management include blood transfusion, antifibrolytics and surgical hemostasis.